Growth habit and gene pool effects on inheritance of yield in common bean - Kornegay, Julia L.; White, Jeffrey W.; Ortíz de la Cruz, O. (Springer, 1992)
To satisfy farmer and consumer preferences, breeding efforts to increase yield potential in common bean must take into account the interrelated effects of growth habit, seed size, maturity, and gene pool on yield expression in segregating populations. To examine the relationships among these traits, a genetic study was conducted to determine the effect of growth habit on yield and seed size in crosses among five bean lines from diverse gene pools. Two parental bean lines had determinate, type I growth habits and large seed size typical of the Neuva Granada-Andean gene pool. Two other lines were tropical Mesoamerican types with type II growth habits and small seed size; and the fifth line, G13625, a landrace of the Jalisco gene pool from the Mexican highlands, had a type IV climbing growth habit and medium seed size. Individual F2 plants from each cross and parental lines were evaluated for growth habit and yield component traits under high input field conditions. The following season, the evaluations were repeated on random F3 plants. Of the five parental lines, only G13625 showed significant GCA effects for yield in both the F2 and F3 generations. Improved yielding ability of G13625 progeny was associated with an increased expression of climbing bean growth habit traits: guide length, climbing ability, node number on main stem, and plant height. Crosses between Andean x Mesoamerican and Andean x Jalisco genotypes, as well between growth habit type I (Andean x Andean) and between type II (Mesoamerican x Mesoamerican) had very low parent-offspring heritability values for yield. Yield heritability was only significant for crosses between Mesomerican x Jalisco gene pools. An apparent simple genetic control of growth habit modification towards semi-climbing and climbing types is proposed as the major reason for increased yields in these crosses. No genetic linkage between genes controlling growth habit and seed size was detected which might restrict the development of high yielding large-seeded type II lines.